2006
DOI: 10.1111/j.1095-8312.2006.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins of viviparity, or reversal from viviparity to oviparity? The European common lizard (Zootoca vivipara, Lacertidae) and the evolution of parity

Abstract: The evolution of viviparity in squamates has been the focus of much scientific attention in previous years. In particular, the possibility of the transition from viviparity back to oviparity has been the subject of a vigorous debate. Some studies have suggested this reversal is more frequent than previously thought. However, none of them provide conclusive evidence. We investigated this problem by studying the phylogenetic relationships between oviparous and viviparous lineages of the reproductively bimodal li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
115
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(128 citation statements)
references
References 35 publications
7
115
0
6
Order By: Relevance
“…Whatever the mechanism that results in this difference, a possible outcome could be retarded skeletal ossification in viviparous hatchlings, as predicted by Maisano (Maisano, 2001). A recent study of 142 populations of L. vivipara identified 48 haplotypes and yielded a robust phylogenetic hypothesis based on molecular genetic data (cytochrome b and 16S ribosomal RNA) (Surget-Groba et al, 2006). This study revealed that viviparous populations are not monophyletic and that either viviparity evolved on three occasions within the species or that there was a single origin of viviparity followed by a reversal back to oviparity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Whatever the mechanism that results in this difference, a possible outcome could be retarded skeletal ossification in viviparous hatchlings, as predicted by Maisano (Maisano, 2001). A recent study of 142 populations of L. vivipara identified 48 haplotypes and yielded a robust phylogenetic hypothesis based on molecular genetic data (cytochrome b and 16S ribosomal RNA) (Surget-Groba et al, 2006). This study revealed that viviparous populations are not monophyletic and that either viviparity evolved on three occasions within the species or that there was a single origin of viviparity followed by a reversal back to oviparity.…”
Section: Discussionmentioning
confidence: 93%
“…One prediction from this model is that females from lineages with viviparous species should produce calcium-rich yolk, and embryos should not be dependent on eggshell calcium. Lacerta (Zootoca) vivipara Jacquin 1787 is one of three lizard species that exhibits interpopulational variation in reproductive mode (Heulin et al, 1993;Fairbairn et al, 1998;Smith et al, 2001;SurgetGroba et al, 2001;Surget-Groba et al, 2006). Females from oviparous populations oviposit eggs with thick eggshells composed of a mat of fibrous protein overlain by a layer of calcium carbonate (Heulin, 1990;Heulin et al, 2002;Heulin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An important feature of the reproductive and developmental biology of Z. vivipara is that each reproductive mode has characteristics that are similar to those of other squamate species that share that reproductive mode, yet viviparity has evolved relatively recently, and perhaps on multiple occasions, within the species (Surget-Groba et al, 2006). In addition to the potential for important contributions to understanding the role of embryonic calcium nutrition in the evolution of reproductive mode, if calcium transport mechanisms are highly conserved, Z. vivipara is an appropriate model for oviparous and viviparous squamate species generally.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent phylogenetic studies on squamate reptiles suggest that parity mode is a more labile trait. Purported shifts from viviparity to oviparity are suggested at both interspecific (Surget-Groba et al, 2006) and at higher taxonomic level (Pyron and Burbrink 2014). The latter one, however, is based on the assumption that transition from viviparity to oviparity is equally probable as a converse one, which is not the case (e.g.…”
Section: Viviparitymentioning
confidence: 99%
“…These two hypotheses are not necessarily mutually exclusive, as in extant reptiles there are at least few species that have both oviparous or viviparous populations (e.g. Surget-Groba et al, 2006).…”
Section: Viviparitymentioning
confidence: 99%